Regeneration of Ribosomes and Ribosomal Ribonucleic Acid During Repair of Thermal Injury to Staphylococcus aureus - Sogin, Stephen J. (1967)
Heating Staphylococcus aureus MF31 at 55 C for 15 min renders the organisms unable to reproduce on agar containing 7.5% NaCl (1). The heated organisms exhibited an extended lag period during which the organisms regained their ability to grow on the 7.5% NaCl-agar. Inhibitor and antibiotic data indicated that protein synthesis is not involved in this recovery process but nucleic acid synthesis is suggested (3). The data presented here further substantiate the noninvolvement of protein synthesis during recovery and further demonstrate the site of the thermally induced nucleic acid lesion. Methylated albumin kieselguhr column analysis showed the lesion site to be the ribosomal ribonucleic acid (rRNA). The rRNA is resynthesized during the extended lag period. Sucrose gradient analysis demonstrated that a ribosomal peak was undetectable subsequent to the thermal treatment, but this peak was regenerated during the recovery period.